2020
DOI: 10.31234/osf.io/e7cgq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How social relationships shape moral wrongness judgments

Abstract: Our judgments of whether an action is morally wrong depend on who is involved and their relationship to one another. But how, when, and why do social relationships shape such judgments? Here we provide new theory and evidence to address this question. In a pre- registered study of U.S. participants (n = 423, nationally representative for age, race and gender), we show that particular social relationships (like those between romantic partners, housemates, or siblings) are normatively expected to serve distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…someone charging a neighbor for babysitting their children) would be seen as immoral in another (e.g. a mother charging her son for help babysitting the grandchildren) (Clark et al, 2020;Earp et al, 2020). This suggests that moral inference from moral principles will be sensitive to the kind of social role or relationship that someone is judging for.…”
Section: Moral Inference From Moral Principles Is Relationship-specificmentioning
confidence: 99%
“…someone charging a neighbor for babysitting their children) would be seen as immoral in another (e.g. a mother charging her son for help babysitting the grandchildren) (Clark et al, 2020;Earp et al, 2020). This suggests that moral inference from moral principles will be sensitive to the kind of social role or relationship that someone is judging for.…”
Section: Moral Inference From Moral Principles Is Relationship-specificmentioning
confidence: 99%
“…People apply different moral motives or values to the behaviors of different targets (Rai & Fiske, 2011;Waytz & Young, 2018). Recent experimental studies found that we do not only judge transgressions or prosocial behaviors differently depending on actors' relationship with the target (Earp et al, 2020;Hughes et al, 2016;McManus et al, 2020); People also react differently to observing close others being victimized, and spare kin and closer, compared to less close, transgressors to third parties from punishment (e.g., Hofmann et al, 2018;Lieberman & Linke, 2007;Weidman et al, 2020). It has been proposed that such effects are at least partly motivated by protecting the mutual relationship (Weidman et al, 2020).…”
Section: Moral Judgment and Close Relationshipsmentioning
confidence: 91%
“…The strength of these social expectations also may vary. Expectations for a romantic partner's behavior may be fundamentally different than those for a stranger (Clark et al, 2020;Earp et al, 2020). Indeed, perceptions of selfishness can be powerfully shaped by whether the relationship between agents is communal or exchange-based (Clark & Mills, 1979;Clark & Mills, 1993), as well as by the strength of the communal relationship when one does exist (Mills et al, 2004)-topics we further discuss in a section ahead.…”
Section: Expectationsmentioning
confidence: 98%